Pharmacokinetics, pharmacodynamics, and tolerability of LC350189, a novel xanthine oxidase inhibitor, in healthy subjects - Yoon, Seonghae (Drug Des Devel Ther, 2015)
INTRODUCTION: LC350189 is a novel selective xanthine oxidase inhibitor under clinical development for the management of hyperuricemia in gout patients. The aim of this study was to evaluate the pharmacokinetics, pharmacodynamics, and tolerability of the drug in healthy subjects. METHODS: A dose-block randomized, double-blind, active and placebo-controlled, single- and multiple-dosing study was conducted. A single ascending dose (SAD) study (10–600 mg) and a multiple ascending dose (MAD) study with once-daily doses (100–800 mg) for 7 days were conducted. Serial samples of blood and urine for pharmacokinetics/pharmacodynamics analysis were collected, and tolerability and adverse events were assessed throughout the study. RESULTS: Sixty-seven and 58 subjects were enrolled in the SAD and MAD studies, respectively. The mean C(max) and AUC(last) values increased with increasing doses, and exposure to LC350189 was dose proportional. The 24-hour mean serum uric acid (C(mean,24)) decreased by 8.7%–31.7% (day 1) and 53.5%–91.2% (day 7) from baseline in the SAD and MAD studies, respectively, and the percentage decrease in C(mean,24) increased with higher doses. CONCLUSION: LC350189 was well tolerated in the dose range of 10–800 mg. It lowered the serum and urine uric acid levels substantially in this dose range; the extent of the decrease in the serum uric acid level in the 200 mg dose group was similar or higher compared to that of febuxostat 80 mg group in the MAD study. It is expected that LC350189 could be safely administered once daily to patients with hyperuricemia or gout, leading to a sufficient decrease in uric acid levels.